Relative Factors of Dental Caries in Child Aged between 0-5 Years in Child Development Centers at Kongkrailas District, Sukhothai Province - Suwonnoparat, Napa (Journal of Health Science of Thailand, 2019)
This study aimed to investigate factors related to dental caries among children aged 0-5 years old. Cross-sectional analysis was applied in the study. The samples were 383 parents of the children aged 0-5 years old purposively selected from 11 children development centers in Kongkrakilas District, Sukhothai Province. Data collection took 3 months, from November 2018 to January 2019. The data was collected through self-administered questionnaires and the findings from oral health examination in children. The data were categorized into 2 groups based on the finding of having and not having tooth decay and dental caries of children; and were analyzed by frequency, percentage and Chi-square test. It was found that the majority of questionnaire responders were mothers of the children. Most of them graduated at primary school level; and had income lower than 5,000 baht per month. Dental caries was observed in 50.4% of the children. In addition, the parents of both children groups (both with and without tooth decay/dental caires) had similar level of knowledge. They could answer 13 questions out of 15 questions. The level of knowledge of parents whose children did not have dental caries was statistically different from those without caries (p<0.05). It was found that more than 90.0% of the parents had a high level of belief and more than 60.0% had a high level of attitude. However, both parent groups had 4 correct behaviors out of 15, and more than 50.0% had performed oral health care behaviors for their children at a moderate level. When analyzing factors related to oral health care, it was found that knowledge, belief and attitude toward oral health care of children significantly influenced parents’ oral health care behavior (p<0.05). Therefore, providing accurate knowledge about dental health care behaviors could help parents to have appropriate behavior for oral health care of their children.